FORMS OF INTERACTION BETWEEN PRESCHOOL EDUCATION ORGANIZATION AND PARENTS (American Journal of Pedagogical and Educational Research, 2024)
The article pays great attention to the interaction between the pedagogical team and parents in preschool education organizations. The main reasons for understanding the peculiarities of managing the quality of interaction in modern changing conditions, where parents have become customers of educational services, are presented.